2002
DOI: 10.1038/sj.jhh.1001301
|View full text |Cite
|
Sign up to set email alerts
|

Office blood pressure variability as a predictor of acute myocardial infarction in elderly patients receiving antihypertensive therapy

Abstract: Larger variability of office blood pressure (BP) was reportedly associated with a higher risk of stroke or mortality from all causes. In the present study, we focused on the relationship of variability of office BP and occurrence of acute myocardial infarction (MI). We registered 139 patients receiving antihypertensive therapy for more than 1 year who experienced first-ever episode of MI at the age of 60 years or over. At least two sex-and age-matched (؎5 years) control patients were registered for every MI pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
3
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 12 publications
3
51
3
4
Order By: Relevance
“…20,21 Further, it has been suggested that increased blood pressure variability may additionally be a manifestation of baroreflex regulation of blood pressure. 3,22 However, previous evidence indicates that decreased (not increased) heart rate variability is associated with an increased risk of mortality, suggesting that heart rate variability does not play a role in the relationship between blood pressure variability and mortality in the current study. 23 Although some have suggested that higher blood pressure variability might identify people with subclinical inflammation, 24 elevated CRP was not associated with increased visit-to-visit variability in systolic blood pressure in the current analysis.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…20,21 Further, it has been suggested that increased blood pressure variability may additionally be a manifestation of baroreflex regulation of blood pressure. 3,22 However, previous evidence indicates that decreased (not increased) heart rate variability is associated with an increased risk of mortality, suggesting that heart rate variability does not play a role in the relationship between blood pressure variability and mortality in the current study. 23 Although some have suggested that higher blood pressure variability might identify people with subclinical inflammation, 24 elevated CRP was not associated with increased visit-to-visit variability in systolic blood pressure in the current analysis.…”
Section: Discussioncontrasting
confidence: 48%
“…11,17,22,26 In a study of 1433 men from the Honolulu Heart Program, visit-to-visit variability in systolic blood pressure was associated with incident coronary heart disease events, even after controlling for potential confounders including average systolic blood pressure across study visits. 27 In a recent publication including the secondary analysis of several randomized controlled trials, higher visit-to-visit variability in systolic blood pressure was associated with an increased incidence of stroke in a cohort of subjects who had previously experienced a transient ischemic attack.…”
Section: Muntner Et Al Visit-to-visit Variability In Blood Pressurementioning
confidence: 99%
“…There are many different ways of expressing blood pressure variability, ranging from beat-to-beat changes 9 to long-term changes between office visits. 10 Although there have been some studies supporting a pathological role of increased variability, 10,11 it remains unclear to what extent such adverse effects are a manifestation of more extensive target organ damage impairing the baroreflex regulation of blood pressure (and hence increasing blood pressure variability) as opposed to a direct effect of the variability itself.…”
Section: Importance Of Blood Pressure Variabilitymentioning
confidence: 99%
“…[7][8][9][10] One drawback of the application of visit-to-visit office BPV for the routine clinical management of hypertension is that obtaining it requires several office visits over a period of time. One possible way to solve this is to evaluate day-by-day home BPV, because this selfmeasurement makes it possible to obtain multiple BP values in a relatively short period under well-controlled conditions.…”
mentioning
confidence: 99%